1999
DOI: 10.1021/cm990506k
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Continuous Mesoporous Silica Film with Fully Aligned Mesochannels on a Glass Substrate

Abstract: A continuous mesoporous silica film with uniaxially aligned hexagonal mesochannels was formed on a silica glass substrate using a rubbing-treated thin polyimide coating on the substrate. Polyimide which has a hexamethylene group per the repeating unit as a part of the main chain was used. The mesostructured silica film was grown on the polyimide-coated substrate through the hydrolysis of tetraethoxysilane under acidic conditions in the presence of hexadecyltrimethylammonium chloride. X-ray diffraction experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 60 publications
6
136
0
Order By: Relevance
“…One of the most successful techniques to date for aligning mesochannels on a global scale (centimetre) has originated from a technique known as 'rubbing', pioneered by researchers at Cannon and Waseda University, and initially demonstrated for mesoporous particles in 1999 and for films in 2000 [5,[75][76][77][78][79][80]. The technique entails using a 10 nm thin polyimide coating to induce preferred unidirectional alignment and orientation of the mesochannels in the overlaying film.…”
Section: Chemical Epitaxymentioning
confidence: 99%
“…One of the most successful techniques to date for aligning mesochannels on a global scale (centimetre) has originated from a technique known as 'rubbing', pioneered by researchers at Cannon and Waseda University, and initially demonstrated for mesoporous particles in 1999 and for films in 2000 [5,[75][76][77][78][79][80]. The technique entails using a 10 nm thin polyimide coating to induce preferred unidirectional alignment and orientation of the mesochannels in the overlaying film.…”
Section: Chemical Epitaxymentioning
confidence: 99%
“…This alignment is passed on to the micellar structure of the surfactant molecules and can lead to a macroscopic alignment of the mesopores. The exact formation mechanism that leads to the alignment seems to depend on the matching of the chain length of the hydrophobic part of the surfactant to the chemical structure of the polyimide underlayer [44,45]. Zhao et al [41] and Naik et al [42] demonstrated that the shear flow exerted on films during dip coating can also influence mesopore alignment to some degree, but the correlation length of the obtained mesostructure might be low in these cases.…”
Section: Thin Film Deposition and Functionalization Techniquesmentioning
confidence: 99%
“…The orientation of the pores directly depends on the self-assembled structure of the surfactant. Uniform alignment of mesoporous silica thin films can be possible under a strong magnetic field or on a rubbed polymer film [154,155]. However, complicated patterning is not simple using these methods.…”
Section: Mesoporous Structurementioning
confidence: 99%